KADAR PROTEIN, AKTIVITAS ANTIOKSIDAN DAN SIFAT ORGANOLEPTIK COOKIES TERSUBSTITUSI TEPUNG MOCAF DAN TEPUNG KECAMBAH KACANG HIJAU KUKUS - Ranum Ester Putri Perdani; Wikanastri Hersoelistyorini; Agus Suyanto (Universitas Muhammadiyah Semarang, 2018)
Cookies are lightly floured cake that has a sweet taste which make it desirable, cookies using flour substituted with mocaf flour and steamed green bean sprout flour. The general purpose of this research is to know protein content, antioxidant activity and organoleptic nature of cookies based on mocaf flour and steamed green bean sprout flour. The experimental method of experimental type using the measured data of protein content and antioxidant activity was tested with Microsoft Excel spreadsheet. The organoleptic properties were statistically analyzed using the Friedman test and the Wilcoxon test. The results of the analysis showed that there was an influence of the amount of substitution of mocaf flour and steamed green bean sprout flour to protein content, antioxidant activity and organoleptic properties. The best results of this study were substituted cookies with 12, 26% protein content on 30% flour formula, 19.47% antioxidant activity on cookies formula 50% and the best organoleptic properties produced from cookies yielded likes on treatments The average organoleptic properties of cookies the panelists say that the color is not being interested is brown color, the aroma that rather favored is fragrant, the unpleasantless crispness is too crunchy, and the unappealingless taste is bitter taste . The Conclusions of the research conducted on cookies substitution of mocaf flour and flour steamed green bean sprouts indicate a real difference for each test performed.